Examining the dual mediation hypothesis under personal nostalgia - Marchegiani, Chris; Phau, Ian (European Institute of Retailing and Services Studies, 2011)
Nostalgia is often examined in the marketing literature as a 'single' response. However, Personal nostalgia as a specific type of nostalgic response is experiencing an increase in investigation within the marketing literature. This nostalgic appeal is also frequently utilized in the marketplace for a range of product categories. Important consumer behavior reactions such as cognitive, attitudinal, and purchase intent responses are all expected to be significantly influenced as a result of the specific nostalgic appeal type used. This research uses regression to examine cognition, attitude towards the advert, attitude towards the brand, and intention to purchase the brand, in consumers experiencing a personal nostalgic response. Although the association between consumer?s cognitive, attitudinal and purchase intent responses to advertising appeals is widely examined, the connection between these reactions when experiencing specifically personal nostalgia have not been empirically examined. The results further the understanding of how this specific type of nostalgia influences these important consumer behavior responses. For mangers, the possible benefits and detrimental effects of using personal nostalgia are examined.